2013
DOI: 10.1007/s00408-013-9480-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aspiration Pressure Over Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration on the Diagnosis of Intrathoracic Lymphadenopathies

Abstract: Negative pressure should be applied in an EBUS-TBNA procedure. Although the diagnostic yield was not different, high negative pressure was superior to low negative pressure in obtaining numbers of adequate cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…They also found that higher negative pressure was superior to lower negative pressure for obtaining adequate cytological specimens. 28…”
Section: Discussionmentioning
confidence: 99%
“…They also found that higher negative pressure was superior to lower negative pressure for obtaining adequate cytological specimens. 28…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported no difference in sample adequacy, sample quality, diagnostic yield and specific diagnostic yield for malignancy [27]. A smaller prospective study by Boonsarngsuk et al [28] compared EBUS-TBNA with different levels of pressure: 0 (no suction), and -20 and -40 cm H 2 O. In this study, only 1 biopsy was performed at each LN with a different pressure level (0, and -20 and -40 cm H 2 O).…”
Section: Results Of Pico Questionmentioning
confidence: 99%
“…On the other hand, few studies have reported better yields with higher suction pressure. Boonsarngsuk et al [8] compared 0 mL, 20 mL, and 40 mL suction pressure in EBUS-TBNA and found no difference in the adequacy and diagnostic yield between 20 mL and 40 mL suction pressure. However, both of these were superior to the results obtained by zero suction.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors are known to influence the yield of EBUS-TBNA, including: the needle size [5], number of passes performed [6], and nodal size [4]. In clinical practice, EBUS-TBNA is commonly performed by applying vacuum suction, although evidence regarding its utility is inconsistent [7,8]. Consequently, a recent technical Working Group report also suggested that EBUS-TBNA may be performed with or without the application of suction [9].…”
Section: Introductionmentioning
confidence: 99%